A Second Wind for Inorganic APIs: Leishmanicidal and Antileukemic Activity of Hydrated Bismuth Oxide Nanoparticles - Andriy Grafov; Ana Flávia da Silva Chagas; Alice de Freitas Gomes; Wessal Ouedrhiri; Pierfrancesco Cerruti; Maria Cristina Del Barone; Breno de Souza Mota; Carlos Eduardo de Castro Alves; Anny Maíza Vargas Brasil; Antonia Maria Ramos Franco Pereira; Gemilson Soares Pontes (MDPI AG, 2024)
American cutaneous leishmaniasis is a disease caused by protozoa of the genus Leishmania. Currently, meglumine antimoniate is the first-choice treatment for the disease. The limited efficacy and high toxicity of the drug results in the necessity to search for new active principles. Nanotechnology is gaining importance in the field, since it can provide better efficacy and lower toxicity of the drugs. The present study aimed to synthesize, characterize, and evaluate the in vitro leishmanicidal and antileukemic activity of bismuth nanoparticles (BiNPs). Promastigotes and amastigotes of L. (V.) guyanensis and L. (L.) amazonensis were exposed to BiNPs. The efficacy of the nanoparticles was determined by measurement of the parasite viability and the percentage of infected cells, while the cytotoxicity was characterized by the colorimetry. BiNPs did not induce cytotoxicity in murine peritoneal macrophages and showed better efficacy in inhibiting promastigotes (IC50 < 0.46 nM) and amastigotes of L. (L.) amazonensis. This is the first report on the leishmanicidal activity of Bi-based materials against L. (V.) guayanensis. BiNPs demonstrated significant cytotoxic activity against K562 and HL60 cells at all evaluated concentrations. While the nanoparticles also showed some cytotoxicity towards non-cancerous Vero cells, the effect was much lower compared to that on cancer cells. Treatment with BiNPs also had a significant effect on inhibiting and reducing colony formation in HL60 cells. These results indicate that bismuth nanoparticles have the potential for an inhibitory effect on the clonal expansion of cancer cells.